To Assess the Correlation Between Financial Instability and the Prevalence of Anxiety and Depression. A Cross-Sectional Study - Muhammad Tauseef Javed, Mamoona Manzoor, Ayesha Javaid, Mian Mukhtar Ul Haq, Manzoor Ali, Junaid Rasool (Pakistan Journal of Medical & Health Sciences, 2023)
Aims and Objectives: This study aimed to assess the correlation between financial instability and the prevalence of anxiety and depression, examining the mediating roles of social support and perceived stress. The objective was to generate evidence-based insights to inform specialized mental health and socioeconomic interventions designed to mitigate psychological distress arising from financial strain. Methodology: This cross-sectional study included adults from various socioeconomic backgrounds in tertiary care hospitals across Pakistan, selected through stratified random sampling. Data were collected via structured interviews and validated self-report questionnaires, including the Generalized Anxiety Disorder-7 (GAD-7) and Patient Health Questionnaire-9 (PHQ-9) for anxiety and depression symptoms. Financial instability was assessed through income-to-needs ratio, employment status, and debt burden, whereas social support and perceived stress were evaluated using standardized scales. Data analysis was performed using SPSS version 27.0, employing multivariate logistic regression and Structural Equation Modeling (SEM) to explore associations after adjusting for demographic variables. Ethical approval was obtained, and informed consent was secured from all participants. Results: Financial instability significantly increased mental health risks, with elevated odds ratios (OR) for low income (OR = 2.31), debt burden (OR = 2.14), and employment insecurity (OR = 2.76). The prevalence of clinically significant anxiety (GAD-7 ≥10) was 28.5%, while depression (PHQ-9 ≥10) was 34.1%. High perceived stress was the strongest predictor of poor mental health outcomes (OR = 4.22, 95% CI: 3.57–5.01), followed by low social support (OR = 1.89, 95% CI: 1.54–2.32). Participants reporting both low social support and high perceived stress faced the highest risk (OR = 5.37, 95% CI: 4.62–6.21). Findings highlight the combined detrimental impact of economic and psychosocial factors on mental health. Conclusion: Financial instability is significantly associated with higher rates of anxiety and depression, with social support and perceived stress playing pivotal mediating roles. Addressing economic challenges alongside implementing targeted mental health interventions is essential to alleviate financial distress, mitigate psychological impacts, and enhance overall well-being. Keywords: Financial instability, Anxiety, Depression, Social support, Perceived stress, Cross-sectional study.